A web-based image recognition system for detecting harumanis mangoes / Mohamad Shahmil Saari, Romiza Md Nor and Huzaifah A Hamid - Saari, Mohamad Shahmil; Md Nor, Romiza; Huzaifah, A Hamid (UiTM Cawangan Perlis, 2020)
Harumanis mango cultivar is special to Perlis (north state of Malaysia) and has been declared in the national agenda as a special fruit. For those who are not acquainted with aromatic mango, it is difficult to tell the distinction between Harumanis and the others. By using image recognition, people can identify Harumanis feature details by image recognition technique where algorithm is applied to recognize the mango. Convolutional neural networks method is a suitable technique for the creation of a multi-fruit in real-time classification sorter with the camera and for the detection of moving fruit. Furthermore, the accuracy of the image classification can be improved by increasing the number of datasets, the distance of images from the camera, and the labelling process. This project used Mobile Net architecture model because it consumes less computational power and it can also provide efficiency of the accuracy. A web-based image recognition system for detecting Harumanis mangoes was developed and known as CamPauh to recognize four classes of mango which are Harumanis, apple mango, other types of mangoes and not mango. CamPauh can identify different type of mangoes and the result was stored into the database and appeared on the website. Evaluation on the accuracy was conducted discussed to support users' satisfaction in identifying the correct mango type.